Determining 1-Yr Prosthetic Use for Mobility Prognoses for Community-Dwelling Adults with Lower-Limb Amputation: Development of a Clinical Prediction Rule. (May 2016) - Wong, Christopher Kevin; Young, Rebecca S.; Ow-Wing, Carlyn; Karimi, Parisa
ABSTRACT: Objective: The objective of this study was to develop a prognostic clinical prediction rule to identify people not achieving community walking level prosthetic use after 1 yr. Design: This is a prospective longitudinal cohort study of community-dwelling adults with lower-limb amputations recruited from support groups and prosthetic clinics. Participants completed Activities-specific Balance Confidence and Houghton prosthetic use for mobility self-report scales and the Berg Balance Scale. The clinical prediction rule was developed using multivariate logistic regression, receiver operating curves, and probability statistics to identify people not achieving community walking level prosthetic use (Houghton scores <9) at 1 yr. Results: Forty (74.1%) of 54 participants provided follow-up data. Participants averaged 57.0 ± 11.9 yrs old, and the most recent amputation had occurred an average of 6.6 ± 11.0 yrs ago. Seventy percent had vascular amputations and 52.5% had transtibial amputations. The clinical prediction rule predicted who would not reach the community prosthetic walking level with excellent accuracy (area under the curve >0.96) using four criteria: initial Houghton, Activities-specific Balance Confidence, and Berg Balance Scale tasks 9 (retrieve object from floor) and 10 (look behind over shoulders). Failure to exceed cutoff scores in two or more criteria yielded posttest probability of not reaching community walking prosthetic use 1 yr later for 90% of participants or higher. Conclusions: Accurate 1-yr prosthetic use for mobility prognoses can be obtained by screening prosthetic use, balance confidence, and balance ability to identify community-dwelling people with lower-limb amputations unlikely to achieve community walking prosthetic use.